Study of some village clusters : socio-economic context of development (Integrated Rural Development Programme (Bangladesh). Statistics, Research, and Evaluation Division. Bench Mark Survey report series, 1976)
Contributed survey reports presented rural socioeconomic data in the context of microlevel planning in Bangladesh.